PENERAPAN MODEL INKURI TERBIMBING UNTUK MENINGKATKAN HASIL BELAJAR SISWA KELAS III SD - Tri Wiyoko; Nidar Astuti (Fakultas Ilmu Pendidikan Universitas Negeri Surabaya, 2020)
Learning in elementary schools that do not innovate with the development of learning models will cause learning processes and outcomes to be low. So there is a need for research to improve the process and student learning outcomes by applying the guided inquiry model. The steps of guided inquiry include (1) orientation, (2) formulating the problem, (3) formulating hypotheses, (4) collecting data, (5) testing hypotheses, and (6) concluding. Classroom action research (CAR) was carried out in class III SD 38 / II Pauh Agung. Data collection techniques consisted of test and non-test techniques. The test technical instrument is in the form of essay test questions. The results of the study concluded that the application of the guided inquiry model for grade III students of SD Negeri 38 / II Pauh Agung could improve the learning process and student learning outcomes. Improved student learning processes can be reviewed from student learning activities by 85.71% with an N-gain score of 0.55 in the medium category and teacher teaching activities by 84.09% with an N-gain score of 0.5 in the medium category. Furthermore, for student learning outcomes that complete KKM increased from cycle I by 40% to 76% in cycle II. So the application of guided inquiry learning models can improve the process and learning outcomes of grade III students.